USE OF DIGITAL AND EDUCATIONAL TECHNOLOGIES IN COMBATING LGBT-PHOBIA: A SYSTEMATIC LITERATURE REVIEW (Editora Impacto Científico, 2025)
This study aims to conduct a systematic literature review on the use of educational and digital technologies to address LGBTphobia within the school context. Considering the persistent cases of discrimination and violence against LGBTQIAPN+ individuals in educational institutions and on social media, it becomes essential to investigate how technological tools can support the development of more inclusive pedagogical practices. The methodology adopted followed the principles of the “state of knowledge” approach, as proposed by Morosini and Fernandes (2014), and was grounded in the theoretical guidelines for bibliographic research presented by Gil (2007). The data collection was carried out using descriptors such as “educational and digital technologies” and “combating LGBTphobia,” covering the period from 2020 to 2024. Searches were conducted in the CAPES Theses and Dissertations Catalog and in Google Scholar. The findings revealed a significant gap in the scientific literature on the subject, as no master’s or doctoral studieswhether academic or professional addressing this topic directly within the defined timeframe were found in the CAPES database. Only one article related to the theme was identified, discussing the use of digital technologies in an educational initiative aimed at confronting violence against the LGBTQIA+ population. Based on this scenario, the study examined the possibilities of using digital technologies as pedagogical tools in combating LGBTphobia, emphasizing their potential to strengthen support networks, increase the visibility of dissident identities, and promote human rights within the school environment. The research also identified key challenges, such as the lack of public policies devoted to the pedagogical use of technologies with a focus on sexual and gender diversity, the need for critical teacher education, and the influence of conservative discourses that hinder the advancement of inclusive practices. The study concludes that, although national scientific literature on the topic remains incipient, the use of educational and digital technologies represents a promising pathway for addressing LGBTphobia in schools. It highlights the importance of fostering further research, institutional policies, and training initiatives that integrate education, diversity, and technology in order to transform schools into truly democratic, safe, and welcoming spaces for all identities.DOI: https://doi.org/10.56238/edimpacto2025.090-084